Evaluation of inflammatory and oxidative profile in patients with recurrent wheezing - Nascimento, Pricila Ferrari Moreira; Oliveira, Leandro Licursi de; Salgado, Patrícia de Oliveira; Silva, Eduardo de Almeida Marques da; Bastos, Daniel Silva Sena; Almeida, Palloma Porto; Freitas, Rodrigo de Barros; Brito, Mirna Peçanha; Marques, Emília Torres Costa; Cardoso, Silvia Almeida (Ciência e Natura, 2022)
Wheezing is a clinical expression of numerous respiratory-related conditions. Although asthma is the leading cause of wheezing during childhood. The present study aims to evaluate the inflammatory and oxidative profile of pediatric patients with recurrent wheezing. Seventy-eight volunteers were divided into three groups according to their age (≤ 36, 36 to 72 and ≥ 73 months). Blood was collected for hematological evaluation, serum detections of total immunoglobulin E (IgE), and C-reactive protein (PCRus). The oxidative profile was evaluated by total antioxidant capacity (FRAP), malondialdehyde (MDA) and carbonylated protein markers. There was no significant difference in the IgE and PCRus levels among the three groups evaluated. However, a significant positive correlation was observed for PCRus with total leukocyte and with neutrophils for the group of patients ≥ 73 months of age. The intermediate age group presented significantly reduced FRAP values in the serum, while significant values of oxidative damage markers were observed in the group of patients ≥ 73 months of age. When determining the correlation between inflammatory and oxidative markers, only the ≥ 73 months group showed significant. The group ≥ 73 months stands out with significant alterations of the oxidative stress markers and their correlations with the inflammatory profile.